A Unique Shrine From the Late Iron Age in Jordan - Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
In October and November of 2014 an archaeological team lead by Lucas Petit of the University of Leiden and Zeidan Kafafi of Yarmouk University uncovered a 2,700-year-old shrine at Tell Damiyah in Jordan. This had been in the center of a small village that had been closely allied with the Neo-Assyrian capital, as is attested by written sources and ceramics. The shrine was in the form of a rectangular building with a platform measuring eight by six metres. The discovery of this shrine is of considerable importance since this is the first late Iron Age shrine to have been brought to light in the region.